2006
DOI: 10.1161/01.atv.0000216406.44762.7c
|View full text |Cite
|
Sign up to set email alerts
|

The Elastic Lamellae of Devitalized Arteries Calcify When Incubated in Serum

Abstract: Objective-To determine whether serum contains an activity that induces artery calcification. Methods and Results-The elastic lamellae of devitalized rat aortas calcify rapidly in rat or bovine serum, or in human serum provided [Pi] Ն2 mmol/L. This calcification is attributable to a potent serum calcification factor (SCF), one that causes devitalized aortas to calcify when incubated in DMEM containing as little as 1.5% serum but not in DMEM alone. The SCF that initiates medial elastin calcification has the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 26 publications
3
53
0
Order By: Relevance
“…It has been repeatedly shown that MGP, although it is a circulating protein, acts as inhibitor of the extracellular matrix calcification in the vicinity of cells expressing the protein. 12,34,37 Therefore, our findings that PXE fibroblasts express lower amount of the g-carboxylated form of MGP compared to controls may suggest that calcification of elastic fibers, at least in the dermis of PXE patients, might depend on local scarce availability of the active carboxylated form of MGP. 26 This hypothesis is in agreement with data obtained on transgenic animals showing that local, and not systemic, expression of MGP inhibits extracellular matrix calcification, 34 and with findings showing that only living smooth muscle cells producing MGP are able to prevent calcification of aortic rings in organ culture.…”
Section: Mgp and Elastic Fiber Calcification In Pxe D Gheduzzi Et Almentioning
confidence: 74%
See 2 more Smart Citations
“…It has been repeatedly shown that MGP, although it is a circulating protein, acts as inhibitor of the extracellular matrix calcification in the vicinity of cells expressing the protein. 12,34,37 Therefore, our findings that PXE fibroblasts express lower amount of the g-carboxylated form of MGP compared to controls may suggest that calcification of elastic fibers, at least in the dermis of PXE patients, might depend on local scarce availability of the active carboxylated form of MGP. 26 This hypothesis is in agreement with data obtained on transgenic animals showing that local, and not systemic, expression of MGP inhibits extracellular matrix calcification, 34 and with findings showing that only living smooth muscle cells producing MGP are able to prevent calcification of aortic rings in organ culture.…”
Section: Mgp and Elastic Fiber Calcification In Pxe D Gheduzzi Et Almentioning
confidence: 74%
“…This is in agreement with recent observations that mature MGP is synthesized by cells in periphery, 34 where it would exert local inhibition of ectopic calcification. 12,34,37 In conclusion, impaired maturation of MGP would be part of the metabolic alterations of PXE fibroblasts and could play a relevant role in time-dependent stability of elastic fibers in PXE.…”
Section: Mgp and Elastic Fiber Calcification In Pxe D Gheduzzi Et Almentioning
confidence: 93%
See 1 more Smart Citation
“…The ability of MGP to inhibit crystal growth depends on the presence of Gla residues, which could bind calcium in both solution and calcium salt crystals. 34,35 But the degree of γ-carboxylation required for MGP to inhibit calcification in humans is not known. In addition to being carboxylated, MGP can also undergo a posttranslational phosphorylation, which is also thought to contribute to its functionality.…”
Section: Discussionmentioning
confidence: 99%
“…34 Thus, disease pathobiology and histological characteristics will differ depending on the mechanisms used to initiate vascular calcium deposition. In early lesions of the Ldlr Ϫ/Ϫ mouse, arterial calcium deposition visualized by Alizarin red staining is overlapping yet distinct from that seen with von Kossa stain for phosphate deposition (unpublished observations); similar observations were noted almost 40 years ago by Puchtler et al in studies of early human atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%